The Precariat as a Phenomenon of the Modern Labour Market in Poland and in the European Union - Knapińska, Magdalena (Studia Oeconomica Posnaniensia, 2014)
The aim of this article is to define precariat, a new notion which describes the status of some social groups in the labour market. An attempt has been made to identify the determinants of this phenomenon as well as its characteristic features, which justify demarcating this group in the labour market. In the first part of the article the notion of precariat is defined in the light of the literature. In the second part, its economic features and scope in Poland are discussed, while the third part focuses on the EU labour market. Finally, in the fourth part, the occurrence of the phenomenon of the precariat in the modern labour market has been assessed. The conclusions stemming from the analysis are included in the final part of the article.